18F-FDG PET/CT in Multisystem Sjögren Syndrome. (May 2015) - Sharma, Punit; Chatterjee, Piyali
Abstract : Abstract: Sjögren syndrome (SS) is an autoimmune disease affecting exocrine glands, mostly lacrimal and salivary glands. Rarely, extraglandular sites such as skin, lung, kidneys, and nervous system may be involved. 18 F-FDG PET/CT can be employed in SS for assessment of disease activity and for exclusion of lymphoma. We here present the case of a 61-year-old woman with SS where multisystem involvement was demonstrated on 18 F-FDG PET/CT.